Bata, bata-- paano ka ginawa? - Rono, Chito S.; Star Cinema Productions (Firm). (Quezon City Star Cinema Productions, 1998)
This is the story of Lea Bustamante, a mother and a woman who lives her life based on her own principles and not upon the dictates of society.
Disc 1 (60 min.) -- disc 2 (50 min.)
VCD.
Based on [Lualhati Bautista]'s novel, "Bata, bata-- paano ka ginawa?" (Carlos Palanca Award for Literature, 1984)
Story and screenplay, Lualhati Bautista ; produced by Malou N. Santos ; directed by Chito S. Rono.
Albert Martinez, Ariel Rivera, Raymond Bagatsing and Vilma Santos.
Keywords: Mothers -- Philippines -- Drama; Feature films -- Philippines